The dark side of coffee. Price war in the German market for roasted coffee - Julia Koerner (Kiel University, Department of Food Economics and Consumption Studies, 2002)
Germany is the second largest coffee market in the world, just overshadowed by the United States. Coffee is the most popular beverage in Germany - in fact more popular than beer. In 1999 the five biggest companies in the raosted coffee market had a combined market share of 84.5%. The market is characterized by fierce competition which continues to squeeze the earnings of the German coffee roasters. The degree of competition was expected to increase even more as a result of a merger in 1997. This paper examines the pricing behavior in the German market for roasted coffee. The second question is whether the degree of competition has changed due to changes in market structure and changes in demand. Changes in market structure are the merger of Tchibo and Eduscho in 1997. Changes in demand are cyclical demand fluctuations - every year before Easter and Christmas. Empirical results are derived using data on the aggregate market for roasted coffee in Germany during 1992:1 to 2000:12 and indicate that the market is suffering on not only a severe price competition, but on price war.
Keywords: 330; Market for roasted coffee; Germany; conjectural variation; market power; simultaneous equation system; GMM; Kaffeeindustrie; Betriebliche Preispolitik; Preiswettbewerb; Kaffeemarkt; Marktstruktur; Deutschland